UWB CMOS low noise amplifier for mode 1 - Zulkifli, T.Z.A. (IEEE Computer Society, 2018)
This paper presents an ultra-wideband 3.1-4.9 GHz low noise amplifier (LNA) employing a sixth-order bandpass Chebyshev filter. The LNA has been designed using Silterra 0.18 Î¼m CMOS technology at 1.8 V power supply. The simulation shows that the LNA attains a power gain of 14.1 dB with an input reflection coefficient less than -10 dB in frequency range of interest, a noise figure of 4.29 dB at 3.8 GHz, gain flatness of Â±0.25 dB, a 1 dB compression point of -17.67 dBm, -6.90 dBm for IIP3 and power dissipation of 4.5 mW excluding the buffer stage. Â© 2017 IEEE.